Factors Influencing the Effectiveness of Online Learning Among University Students at Universiti Sains Malaysia - Kok Ban Teoh; Lian Xiang Wong; Pei Fang Wong; Shuang Er Wong; Ji Yan Wong; Priya Raj; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
Online learning continues to remain an important mode of delivery in higher education, including at Universiti Sains Malaysia (USM) even after the return to physical classroom settings. However, the effectiveness of online learning is still debated, as different studies have reported mix outcomes. Therefore, this study aims to identify the factors influencing the effectiveness of online learning among students at USM. A quantitative research design was adopted, and an online questionnaire was distributed to 150 USM students who have participated in online learning. The data will be analyzed using SPSS to examine the relationships between the factors studied. The findings indicate that teaching presence, and technology usability contribute significantly to the effectiveness of online learning, while student engagement influence it indirectly. Overall, this study provides valuable insights that can help USM and Malaysian higher education improve online learning strategies, enhance digital teaching practices, and strengthen the delivery quality of online education within Malaysian higher education.